Serum selenium concentration and antioxidant activity in cervical cancer patients before and after treatment - Subramanyam D.; Subbaiah, K.C.V.; Rajendra W.; Lokanatha V. (Experimental Oncology, 2013)
Aim - in the present study, the effect of chemo and radio therapies on serum trace elements content and antioxidant activity in blood serum of cervical cancer patients was evaluated. Among 104 cervical cancer patients selected for the present study, 54 and 50 patients were treated with chemo- and radiotherapy respectively. Plasma Se, Zn, Cu and some enzymatic antioxidants activities were estimated in serum before and after the treatment. The decreased levels of serum trace elements, glutathione peroxidase activity and total antioxidant capacity, and increased malondialdehyde, glutathion reductase was observed in cervical cancer patients when compared to healthy controls. The increased concentration of serum Se, Zn was observed in patients treated with chemotherapy. Simultaneously there was a significant (P << 0,001) increase in glutathione peroxidase and total antioxidant capacity, and significant decrease (P << 0,05) in malondialdehyde and glutathion reductase levels in the serum of patients treated with chemotherapy compared to the patients treated with radiotherapy. Key Words: cervical cancer, free radicals, glutathione peroxidase, selenium, chemotherapy, radiotherapy.